The left atrioventricular valve regurgitation after the surgical repair of the partial atrioventricular canal. Long-term follow-up - Wójcik, Anna; Klisiewicz, Anna; Szymański, Piotr; Lech, Agnieszka; Różański, Jacek; Kuśmierczyk, Mariusz; Hoffman, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction: An ostium primum atrial septal defect (ASD I) accounts for 15-20% of all atrial septal defects. It is usually associated with left atrioventricular valve (LAVV) cleft and regurgitation. Aim of the study : To evaluate the degree of LAVV regurgitation and its pathophysiological significance following surgical correction of ASD I. Material and methods : We examined 41 patients (32 females, 78%) following ASD I closure, including 35 patients following LAVV cleft repair. Their mean age at surgery was 31.3 ±15.6 and at follow-up 39.2 ±14.0 years. LAVV regurgitation was assessed with transthoracic echocardiography, both qualitatively using 4+ scale and quantitatively by effective regurgitant orifice area (EROA), and defined as significant if LAVV regurgitation was ≥ 3+ and/or EROA ≥ 0.40. 13 healthy volunteers served as controls. Results : LAVV regurgitation was present in 40 (97.6%) patients. Compared to controls, in patients following ASD I repair, RVSP was significantly higher and left atrial diameter was significantly larger both in a subgroup of patients with and without significant LAVV regurgitation. Neither age at surgery, nor age at follow-up or left atrial diameter, or RVSP were independently associated with the presence of significant LAVV regurgitation in patients following ASD I repair. Conclusions : LAVV regurgitation is often present following ASD I surgery. The echocardiographic evaluation of RVSP and left atrium diameter is limited in estimation of significance of LAVV regurgitation because of its complex mechanism and persistent consequences of left-to-right shunt. A remote valve repair efficiency is determined mainly by cardiac surgery.